2016
DOI: 10.1039/c6ee01352j
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective in bio-refining: levoglucosenone and cleaner lignin from waste biorefinery hydrolysis lignin by selective conversion of residual saccharides

Abstract: The sustainability of biorefineries can be improved through levoglucosenone production from residual sugars in waste lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…[10] For example, LGO can be synthesized from ad iverse range of biomass sources, such as larch log, [11] bagasse, [12] poplar wood, [13] corn cob, [14] crude waste softwood, [10] and bilberryp resscake. [10] For example, LGO can be synthesized from ad iverse range of biomass sources, such as larch log, [11] bagasse, [12] poplar wood, [13] corn cob, [14] crude waste softwood, [10] and bilberryp resscake.…”
Section: Synthesis Of Levoglucosenone and Cyrenementioning
confidence: 99%
See 1 more Smart Citation
“…[10] For example, LGO can be synthesized from ad iverse range of biomass sources, such as larch log, [11] bagasse, [12] poplar wood, [13] corn cob, [14] crude waste softwood, [10] and bilberryp resscake. [10] For example, LGO can be synthesized from ad iverse range of biomass sources, such as larch log, [11] bagasse, [12] poplar wood, [13] corn cob, [14] crude waste softwood, [10] and bilberryp resscake.…”
Section: Synthesis Of Levoglucosenone and Cyrenementioning
confidence: 99%
“…Cyrene (2)h as been synthesized fromanumber of different biomass starting materials under av ariety of conditions, but most of these processes initially form LGO levoglucosenone (LGO, 1;T able 1). [10] For example, LGO can be synthesized from ad iverse range of biomass sources, such as larch log, [11] bagasse, [12] poplar wood, [13] corn cob, [14] crude waste softwood, [10] and bilberryp resscake. [15] The mosts tudied and highest yielding biomass precursor for the synthesis of LGO is cellulose.…”
Section: Synthesis Of Levoglucosenone and Cyrenementioning
confidence: 99%
“…A thorough study of the relevant variables of the pyrolytic process has demonstrated that temperature, pressure and catalyst concentration, heat and mass transfer are the main factors. It has been reported that the acid‐catalyzed pyrolysis process allows increasing the selectivity towards levoglucosenone, when using glucose, cellulose or birch and pine wood among different biomass sources, and phosphoric acid as a catalyst, under conventional thermal pyrolysis , . The use of solid superacids and zeolites as acid catalysts was also investigated, as well as the effect of ionic liquids .…”
Section: Preparation Of Levoglucosenonementioning
confidence: 99%
“…Cheaper crude oil makes the pursuit of biofuel less lucrative and jeopardizes the pursuit of biorefining. This could, however, be overcome by expanding the product repertoire of a biorefinery through biomass conversion to platform chemicals, analogous to a petrochemical refinery . Indeed, even petrochemical refineries earn half of their revenue from a significantly smaller business volume of chemicals (~16%) compared to that of oil (76%) .…”
Section: Introductionmentioning
confidence: 99%
“…This could, however, be overcome by expanding the product repertoire of a biorefinery through biomass conversion to platform chemicals, analogous to a petrochemical refinery. 2 Indeed, even petrochemical refineries earn half of their revenue from a significantly smaller business volume of chemicals (~16%) compared to that of oil (76%). 3 Biomass valorization to produce chemicals in conjunction with biofuel is imperative for a sustainable and fiscally resilient biorefinery.…”
Section: Introductionmentioning
confidence: 99%